Impact of tornadoes on hospital admissions for acute cardiovascular events. Issue 5 (November 2015) - Silva-Palacios, Federico; Casanegra, Ana Isabel; Shapiro, Alan; Phan, Minh; Hawkins, Beau; Li, Ji; Stoner, Julie; Tafur, Alfonso
Abstract: Background: There is a paucity of data describing cardiovascular events after tornado outbreaks. We proposed to study the effects of tornadoes on the incidence of cardiovascular events at a tertiary care institution. Population and methods: Hospital admission records from a single center situated in a tornado-prone area three months before and after a 2013 tornado outbreak were abstracted. To control for seasonal variation, we also abstracted data from the same period of the prior year (control). Hospital admissions for cardiovascular events (CVEs) including acute myocardial infarction, stroke and venous thromboembolism (VTE) were summated by zip codes, and compared by time period. . Results: There were 22, 607 admissions analyzed, of which 6, 705 (30%), 7, 980 (35%), and 7, 922 (35%) were during the pre-tornado, post-tornado, and control time frames, respectively. There were 344 CVE in the controls, 317 CVE in pre-tornado and 364 CVEs in post tornado periods. There was no difference in the prevalence of CVE during the post-tornado season compared with the control (PPR = 1.05 95% CI: 0.91 to 1.21, p = 0.50) or the pre-tornado season (PPR = 0.96, 95% CI: 0.83 to 1.21, p = 0.63). Conclusion: In conclusion, tornado outbreaks did not increase the prevalence of cardiovascular events. In contrast to the effect of hurricanes, implementation of a healthcare policy change directed toward the early treatment and prevention of cardiovascular events after tornadoes does not seem warranted. Graphical Abstract: Graphic 1 : Zipcode map, CVE admissions per 100.000. Upper left: United States map, Oklahoma in red. Upper right: Oklahoma State map, county of interest in red. CVE: cardiovascular event. IQR: inter-quartile range. Highlights: We analyzed 22, 607 hospital encounters centered on the occurrence of 2 highly destructive tornadoes in the zone. Prevalence proportion ratio of cardiovascular events was not different on the 3-month period before and after tornadoes. Healthcare policy change for the early treatment and prevention of cardiovascular events after tornadoes is not warranted.